Gottfried Wilhelm Leibniz: Dynamica de Potentia et Legibus Naturae Corporeae Tentamen Scientiae Novae: Vol. I - Costa, Andrea; Fichant, Michael; Pasini, Enrico (Georg Olms Verlag, 2023)
Leibniz planned to publish the great Treatise on the Dynamica, written during his Italian journey (1689-90). In the end, however, he decided against publication, and the text was not edited until 1860 by Gerhard. The present critical edition is unique in that it brings together all of Leibniz's autograph drafts, the intermediate copies and the final copy intended for publication. It also aims to reconstitute Leibniz’s complete editorial plan, by adding to it the appendices (Miscellanea), articles published in scholarly journals and studies on various subjects of astronomy and natural philosophy, which Leibniz had planned to append to the main work.